Single-cell RNA-seq reveals a repair pattern in cystic lesions in steroid induced osteonecrosis of the femoral head - Peng, Peng; Tian, Jiaqing; Lin, Kun; Fang, Weihua; Yao, Fangming; Yang, Xiaoqiang; Hou, Wenyuan; Xiao, Fangjun; Lu, Shun; He, Wei; He, Mincong; Xiao, Huan; et al. (Frontiers in Immunology, 2025)
BackgroundStudies have indicated that cystic lesions play a crucial role in the repair processes of steroid-induced osteonecrosis of the femoral head and its subsequent collapse. Here, we employed single-cell RNA sequencing (scRNA-seq) technology to investigate the transcriptomic landscape and repair mechanisms of cystic lesions in SIONFH.MethodsWe applied scRNA-seq combined with computational approaches to characterize distinct cell subsets and their molecular signatures within cystic lesions from three SIONFH patients. Additionally, histological assays were conducted to observe pathological manifestations of these lesions.ResultsEight cell types were identified in cystic lesions of SIONFH. Among them, chondrocytes were divided into five subgroups. Among them, chondrocytes were divided into five subgroups: homeostatic chondrocytes (HomC), fibrocartilage chondrocytes (FC), prehypertrophic chondrocytes (preHTC), inflammatory chondrocytes (InflamC), and hypertrophic chondrocytes (HTC). Additionally, histological assays showed the presence of chondrocytes and a transition zone from chondrocytes to bone tissue within the cystic lesions. Notably, we report that one of the HTC clusters with CLIC3+ expression exhibited a strong involved in bone mineralization, osteoblast differentiation, and cell differentiation.ConclusionWe have delineated the cellular heterogeneity and molecular signatures of cystic lesions in SIONFH. The results reveal a distinct repair program within these lesions, which might be driven by chondrocyte hypertrophy and might culminate in osteogenic differentiation.